2011
DOI: 10.1038/eye.2011.211
|View full text |Cite
|
Sign up to set email alerts
|

Corneal hysteresis in patients with dry eye

Abstract: Purpose To measure corneal hysteresis and intraocular pressure (IOP)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 19 publications
4
10
0
Order By: Relevance
“…Conflicting results are available in the literature regarding central corneal thickness in DED. Although few studies showed similar values between DED patients and normal subjects[2427], we found significantly lower values in patients with oGVHD compared to controls, in agreement with others. [32–34] The corneal thinning in DED is attributed to the increased osmolarity of the tear film that induces the activation of the inflammatory cascade and stimulate the production of high levels of the cytokine and MMP-9 by the distressed epithelial cells.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Conflicting results are available in the literature regarding central corneal thickness in DED. Although few studies showed similar values between DED patients and normal subjects[2427], we found significantly lower values in patients with oGVHD compared to controls, in agreement with others. [32–34] The corneal thinning in DED is attributed to the increased osmolarity of the tear film that induces the activation of the inflammatory cascade and stimulate the production of high levels of the cytokine and MMP-9 by the distressed epithelial cells.…”
Section: Discussionsupporting
confidence: 92%
“…CorVis ST is a device that employs an ultrahigh speed Scheimpflug camera to record dynamic deformation of the cornea. Impaired values of corneal biomechanics have been reported in DED patients with and without Sjögren’s syndrome[24–26]; conversely, Firat et al[27] reported no alterations of corneal biomechanical parameters in patients with DED. However, this study did not evaluate comprehensively ocular surface parameters, and did not stratify patients according to the severity of DED.…”
Section: Discussionmentioning
confidence: 99%
“…Fraunfelder reported corneal problems, such as keratitis, corneal opacity, corneal ulceration, and keratoconus, as the second most prevalent adverse effect among patients during isotretinoin treatment [ 21 ]. Firat and Doganay conducted a study in patients with dry eye and concluded that CH and CRF are not influenced by dry eye [ 22 ]. We would like to investigate whether the changes in precorneal tear film properties induced by isotretinoin have an effect on the corneal biomechanics measured with ORA.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is a study show that dry eye does not affect biomechanical measurements with ORA. 27 The second limitation of this study is the absence of assessment of dry eye test results when comparing groups. In further studies the effect of dry eye could be taken into consideration to more properly interpret the results.…”
Section: Discussionmentioning
confidence: 99%